Micro-trench experiments on interflow and lateral pesticide transport in a sloped soil in Northern Thailand - G. Kahl (2018)
During recent decades, a change in land use in the mountainous regions of Northern Thailand has been accompanied by an increased input of agrochemicals. We identified lateral water flow and pesticide transport pathways and mechanisms in a Hapludult on a sloped litchi orchard in Northern Thailand. During two rainy seasons, two micro-trench experiments were performed at the plot scale (2 by 3 m). The first experiment was performed at the footslope of the orchard; the second was performed at a midslope position. Two salt tracers (bromide and chloride) and two pesticides {methomyl [S-methyl-N-(methylcarbamoyloxy) thioacetimidate] and chlorothalonil (2,4,5,6-Tetrachlor-1,3-benzdicarbonitril)} were applied in stripes parallel to the slope 150 and 300 cm away from the trench. At the trench, soil water was collected by wick samplers. Tensiometers and time-domain reflectometry probes were installed. At the end of the experiment, soil samples were taken and analyzed for residual concentrations of tracers and pesticides. Lateral subsurface flow of water occurred exclusively along preferential flow paths and was mainly observed at 0- to 30- and 60- to 90-cm depth. Lateral transport of pesticides was negligible, but both pesticides were found beneath the application area at 90 cm depth. Therefore, they may pose a groundwater contamination risk. The amount of wick flow and the location of interflow were mainly a function of rain amount and antecedent soil water suction. During dry periods, water flow was restricted to the topsoil. After heavy rain events and wet periods, interflow was mainly observed in the subsoil. The cumulative rain amount between samplings necessary to induce interflow was 20 mm. At the footslope, the interflow was seven times higher, and the network of water-bearing pores increased compared with the midslope position. © ASA, CSSA, SSSA.